Correlation Between Locus of Control with Student’s Social Loafing in Group Task - Priscilla Deborah Rouly Simanjuntak; Rika Eliana (International Journal on Social Science, Economics and Art, 2020)
This study aims to determine the relationship between locus of control and social loafing of students on group-based tasks. The results of the study of 300 students in the University of North Sumatra showed there is a positive relationship between locus of control and social loafing. The data obtained in this study indicates that the more internal a person's locus of control, the lower the tendency to decrease their effort on working in a group. The majority of subjects have lowtendency to do social loafing and prefer to work in small groups. There is no gender difference either in subject‟s locus of control or on the tendency to do social loafing. Collectivistic belief in Indonesian society may be one of the causes of students‟s low tendency to do social loafing